1995
DOI: 10.1172/jci118151
|View full text |Cite
|
Sign up to set email alerts
|

Localization and rapid regulation of Na+/myo-inositol cotransporter in rat kidney.

Abstract: myo-Inositol, a major compatible osmolyte in renal medulla, is accumulated in several kinds of cells under hypertonic conditions via Na+/myo-inositol cotransporter (SMIT). To investigate the physiological role of the SMIT, we sought to determine its localization by in situ hybridization and its acute regulation by NaCl and furosemide administration. Northern analysis demonstrated that SMIT is strongly expressed in the medulla and at low levels in the cortex of kidney. Intraperitoneal injection of NaCI rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 20 publications
6
32
0
Order By: Relevance
“…To extend this observation to an in vivo model, we subjected male Sprague-Dawley rats to 24 hours of water deprivation, a procedure that is known to increase urine osmolality (4,8,10,26,43) and renal medullary sodium concentration (4,42,43). As shown in Table 1, water deprivation resulted in a significant increase in urine osmolality (~40% increase over the baseline urine osmolality).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…To extend this observation to an in vivo model, we subjected male Sprague-Dawley rats to 24 hours of water deprivation, a procedure that is known to increase urine osmolality (4,8,10,26,43) and renal medullary sodium concentration (4,42,43). As shown in Table 1, water deprivation resulted in a significant increase in urine osmolality (~40% increase over the baseline urine osmolality).…”
Section: Figurementioning
confidence: 99%
“…We have also demonstrated that hypertonicity increases expression of the type A natriuretic peptide receptor (NPR-A) (41), a guanylyl cyclase-linked receptor that binds both atrial natriuretic peptide (ANP) and the B-type natriuretic peptide (BNP), leading to an increase in renal excretion of sodium. Water deprivation leads to increased renal medullary sodium concentration (4,42,43). We reasoned that tonicity-dependent stimulation of Sgk1 and subsequent activation of NPR-A gene expression might be linked to the dehydration natriuresis described above.…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridization study indicated that SMIT predominantly expressed TALH (16), where a large transepithelial osmotic gradient exists (Fig. 4) (20).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous report (15) showed that SMIT mRNA abundance was highest in the outer medulla rather than in the inner medulla, and a small but significant amount of SMIT mRNA was present in the cortex. SMIT mRNA in the cortex as well as that in the medulla was significantly induced by dehydration.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation